Amplification Pattern of Partial Gene BMP-15 and GDF-9 in Bali Cattle - Sri Rahayu; M. Sasmito Djati; Agatha Maria Dian Kusumawati; Oktavia Fitri Santika (Natural B, Journal of Health and Environmental Sciences, 2012)
The aim of this research was to determine the polymorphisms of BMP-15 and GDF-9 gene of Bali cattle. DNA was isolated from blood samples of six female cattles with salting out method. Quantitative and qualitative analysis of DNA was measured using spectrophotometer and agarose gel electrophoresis. To get DNA fragment BMP-15 gene was amplified using Forward (5’- AGTTTGTACTGAGCCGGTCT -3'), Reverse (5’- CTGACACACGAA GCGGAGT -3’), while to get DNA fragmen GDF-9 gene was amplified using Forward primer (5’-CAAGGAGGGGACCCCTAAAT-3’), reverse primer (5’- ACCAGAGGCTCAAGAGGAGC- -3’) for GDF-9. The results of amplification showed 4 haplotypes for BMP-15 and GDF-9 gene. It was concluded that there is polymorphism of BMP-15 and GDF-9 gene of Bali cattle.